2009
DOI: 10.1159/000228645
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis by <i>Bartonella</i><i>quintana</i> Masquerading as Antineutrophil Cytoplasmic Antibody-Associated Small Vessel Vasculitis

Abstract: The Bartonella species have been recently recognized as important causative agents of culture-negative bacterial endocarditis. Antineutrophil cytoplasmic antibodies (ANCAs) have been associated with the spectrum of idiopathic small vessel vasculitis. However, a variety of infections can result in a false-positive ANCA test, and especially subacute bacterial endocarditis (SBE) with the presence of ANCAs occasionally mimics the clinical manifestations of an ANCA-associated vasculitis such as skin purpura and glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…Aslangul also describes the interesting finding of ANCA positivity in 10 of 25 patients with Bartonella quintanaor Bartonella henselae-associated IE; among the 8 patients in whom the serologic diagnosis was confirmed by molecular analysis of heart valve tissue, ANCA was found in 6 (1). The possibility that Bartonella, a relatively uncommon cause of IE (2,3), has a close association with ANCA is further supported by observations described in several analogous case reports (4)(5)(6)(7)(8). Likewise, in our series of 109 patients with IE, the only 2 whose IE was caused by Bartonella species both tested positive for ANCA.…”
Section: Replysupporting
confidence: 86%
“…Aslangul also describes the interesting finding of ANCA positivity in 10 of 25 patients with Bartonella quintanaor Bartonella henselae-associated IE; among the 8 patients in whom the serologic diagnosis was confirmed by molecular analysis of heart valve tissue, ANCA was found in 6 (1). The possibility that Bartonella, a relatively uncommon cause of IE (2,3), has a close association with ANCA is further supported by observations described in several analogous case reports (4)(5)(6)(7)(8). Likewise, in our series of 109 patients with IE, the only 2 whose IE was caused by Bartonella species both tested positive for ANCA.…”
Section: Replysupporting
confidence: 86%
“…Aslangul also describes the interesting finding of ANCA positivity in 10 of 25 patients with Bartonella quintanaor Bartonella henselae-associated IE; among the 8 patients in whom the serologic diagnosis was confirmed by molecular analysis of heart valve tissue, ANCA was found in 6 (1). The possibility that Bartonella, a relatively uncommon cause of IE (2,3), has a close association with ANCA is further supported by observations described in several analogous case reports (4)(5)(6)(7)(8). Likewise, in our series of 109 patients with IE, the only 2 whose IE was caused by Bartonella species both tested positive for ANCA.…”
Section: Replysupporting
confidence: 85%
“…Patients with IE mimicking AAV with positive cANCA and antiPR3 have been reported 2 1012. Chirinos et al 10 reported a patient with IE and a positive cANCA whose blood and aortic valve cultures were positive for Enterococcus faecalis .…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified eight patients with IE who were positive for cANCA: seven had peripheral blood cultures positive for viridans streptococcus and one had a negative blood culture but positive valve culture 10. Culture negative B quintana endocarditis mimicking AAV has been reported 11. Peripheral blood cultures were negative for growth but B quintana was identified by PCR amplification, restriction fragment length polymorphism analysis of genomic DNA from the resected aortic valve and positive serology for B quintana and B henselae .…”
Section: Discussionmentioning
confidence: 99%